1999
DOI: 10.1097/00005768-199901000-00025
|View full text |Cite
|
Sign up to set email alerts
|

Pre-exercise carbohydrate meals: application of glycemic index

Abstract: These results suggest a pre-exercise LGI may positively affect maximal performance following sustained exercise. The LGI maintained higher plasma glucose levels at the end of 2 h of strenuous exercise than the HGI, which may have better supported subsequent maximal effort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
103
3
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(119 citation statements)
references
References 25 publications
10
103
3
1
Order By: Relevance
“…In our study an initial increase of glucose was observed and then plateaued whereas insulin continued to increase up to 30 minutes following the ingestion of foods. The same glucose and insulin response prior to exercise was seen in De Marco et al study when the same amount of carbohydrates was ingested [17]. This response of glucose and insulin is common since the initial increase in glucose constitutes the main stimulus for the delayed insulin increase.…”
Section: Discussionmentioning
confidence: 59%
See 4 more Smart Citations
“…In our study an initial increase of glucose was observed and then plateaued whereas insulin continued to increase up to 30 minutes following the ingestion of foods. The same glucose and insulin response prior to exercise was seen in De Marco et al study when the same amount of carbohydrates was ingested [17]. This response of glucose and insulin is common since the initial increase in glucose constitutes the main stimulus for the delayed insulin increase.…”
Section: Discussionmentioning
confidence: 59%
“…On the other hand, there are several studies that examined the effects of different GI foods, at different times prior to exercise, on exercise performance and substrate metabolism that suggest an improvement of exercise performance following LGI food consumption prior to exercise [17,36-40]. Thomas et al [36] were amongst the first ones that expressed interest in the role of GI in sports nutrition.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations